2016
DOI: 10.1016/j.bpg.2016.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for neoplasia in the pancreas

Abstract: Despite its low incidence in the general population, pancreatic cancer is one of the leading causes of cancer-related mortality. Survival greatly depends on operability, but most patients present with unresectable disease. Therefore, there is great interest in the early detection of pancreatic cancer and its precursor lesions by surveillance. Worldwide, several programs have been initiated for individuals at high risk for pancreatic cancer. Their first results suggest that surveillance in high-risk individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 140 publications
(130 reference statements)
0
11
0
1
Order By: Relevance
“…Individuals with both a family history and a pathogenic germline variant may benefit most, as they have been found to be at the highest risk of pancreatic cancer in screening studies, compared with individuals with a family history by no identifiable mutation [144]. Several screening approaches have been taken, but most rely on endoscopic ultrasound (EUS) combined with magnetic resonance imaging or computed tomography (CT) scanning [145][146][147]. Preliminary results from EUS-based screening trials have demonstrated that asymptomatic precursor lesions and, rarely, early curable cancers can be detected, and SEER data hint that more early stage cancers are now being detected nationally [145][146][147][148][149].…”
Section: Screening In Familial Syndromesmentioning
confidence: 99%
“…Individuals with both a family history and a pathogenic germline variant may benefit most, as they have been found to be at the highest risk of pancreatic cancer in screening studies, compared with individuals with a family history by no identifiable mutation [144]. Several screening approaches have been taken, but most rely on endoscopic ultrasound (EUS) combined with magnetic resonance imaging or computed tomography (CT) scanning [145][146][147]. Preliminary results from EUS-based screening trials have demonstrated that asymptomatic precursor lesions and, rarely, early curable cancers can be detected, and SEER data hint that more early stage cancers are now being detected nationally [145][146][147][148][149].…”
Section: Screening In Familial Syndromesmentioning
confidence: 99%
“…The goal is to detect stage one PDAC or, preferably, high-grade precursor lesions [2]. However, especially in small lesions, imaging techniques may not be able to distinguish malignancy and high-grade precursors from benign disease [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Screening is not currently recommended for the general population (US Preventive Services Task Force gives a D recommendation) [7]. However, some have suggested that screening patients at high risk of developing pancreatic cancer is feasible, while acknowledging that data for cost-effectiveness and benefit are still required [8]. To date, the most suitable imaging technology for such screening is unclear [5].…”
mentioning
confidence: 99%